Information Model for Basic Education Core Curriculum Management in Thai Supply Chain - Artaphon Chansamut (International Journal of Supply Chain Management, 2022)
This research aimed to develop and to evaluate information model for basic education core curriculum management in Thai supply chain. The samples are ten experts in the field of information ,supply chain and curriculum . The data is analysed by means and standardized deviations. The research result shows that the model consists of five elements namely main components, Suppliers, school , Learners have completed and customers The assessment of model using Black-Box technique. The research findings revealed that the model is appropriate at the high level that mean The model to support sustainable information system development.